Kinetics study of oil extraction from Citrus auranticum L. by solvent-free microwave extraction - Kusuma, Heri Septya; Amelia, Prilia Dwi; Admiralia, Cininta; Mahfud, Mahfud (Communications in Science and Technology, 2016)
Citrus and its oil are of high economic and medicinal value because of their multiple uses, such as in the food industry, cosmetics and folk medicine. The aim of this study is to investigate the potential of solvent-free microwave extraction for the extraction of essential oils from Citrus auranticum L. peels. Specifically, this study verifies the kinetics based on second-order model and mechanism of solvent-free microwave extraction of Citrus auranticum L. peels. Solvent-free microwave extraction is used to extract essential oils from Citrus auranticum L. peels. The initial extraction rate, the extraction capacity and the second-order extraction rate constant were calculated using the model. Using a three-step experimental design of the kinetics of oil extraction from Citrus auranticum L. peels by solvent-free microwave extraction, this study showed that the extraction process was based on the second-order extraction model. The initial extraction rate (h), the extraction capacity (CS), the second-order extraction rate constant (k), and coefficient of determination (R2) was 0.7483 g L-1 min-1, 0.7291 g L-1, 1.4075 L g-1 min-1 and 0.9992, respectively.